The impact of precession on the observed population of ULXs - Khan, Norman; Middleton, Matthew J.; Wiktorowicz, Grzegorz; Dauser, Thomas; Roberts, Timothy P.; Wilms, Jörn (Monthly Notices of the Royal Astronomical Society, 2022)
The discovery of neutron stars (NSs) powering several ultraluminous X-ray sources (ULXs) raises important questions about the nature of the underlying population. In this paper, we build on previous work studying silated populations by incorporating a model where the emission originates from a precessing, geometrically beamed wind-cone, created by a supercritical inflow. We obtain estimates - independent of the prescription for the precession period of the wind - for the relative number of ULXs that are potentially visible (persistent or transient) for a range of underlying factors such as the relative abundance of black holes or NSs within the population, maxim precessional angle, and low-mass X-ray binary duty cycle. We make initial comparisons to existing data using a catalogue compiled from XMM-Newton. Finally, based on estimates for the precession period, we deteine how the eROSITA all-sky survey (eRASS) will be able to constrain the underlying demographic.
CRIS-Team Scopus Importer:2021-12-24
Keywords: binaries; black holes; neutron; stars; stars; X-rays